Significance of Endoscopic Redness of Duodenum in Health Checkup - Atsushi Nakayama; Motohiko Kato; Yoshiki Sakaguchi; Yu Takahashi; Shinya Kodashima; Ai Fujimoto; Nobutake Yamamichi; Kazumasa Miki; Naohisa Yahagi (JGH Open)
ABSTRACT Background and Aim It is important for endoscopist to diagnose the lesion redness. In this study, we focused on the redness of duodenal bulb. We objectively analyzed the changes in redness of the duodenal bulb using linked color imaging (LCI) with chromatic indicators. Methods Seven endoscopists observed the duodenal bulb with white light imaging (WLI) and LCI, and evaluated them by visual analogue scale (VAS) for the degree of redness. The difference in VAS between WLI and LCI was defined as ΔVAS. All images were quantified by the Comission Internationale de l'Eclariage‐L*a*b* color space. Values related to color differences (ΔE*, ΔL*, Δa*, and Δb*) were calculated from the two images of WLI and LCI. Multiple regression analysis was performed for the factors with the health checkup correlated with ΔVAS and the correlation between ΔVAS and ΔE*, ΔL*, Δa*, and Δb* was also examined. Results The analysis prospectively included 1144 examinees. In multiple regression analysis, it revealed that sex (β = 0.5847, p < 0.0001) and metabolic syndrome (β = 0.4138, p = 0.0012) were the factors independently influenced ΔVAS. And only Δa*, a chromatic index for changes in the degree of redness, showed a statistically and considerably positive correlation with ΔVAS (r = 0.4529, p < 0.0001). Conclusion To evaluate the difference in the degree of redness between WLI and LCI of duodenal bulb in esophagogastroduodenoscopy may help in early detection of metabolic syndrome, which rarely has symptoms.